Proposal for the upgrading of foreign language teaching in secondary schools in St. Vincent and the Grenadines - St. Vincent and the Grenadines. Ministry of Education, Culture, Youth and Women's Affairs (Education Planning Unit, 1992)
Under the programme for Rationalizing the Operations of Newer Secondary Schools (June 1998), the teaching of foreign languages was virtually eliminated from the curriculum in St. Vincent and the Grenadines. This proposal examines the following: 1) student enrolment in foreign languages, 2) foreign language results, and 4) foreign language teachers. Based on this analysis, recommendations are made for the re-introduction and further development of foreign languages in secondary schools. It is hoped that these would provide the basis for formulating a policy with regards to the teaching of foreign languages at both the formal and non-formal levels.
Keywords: foreign languages; secondary schools